2017
DOI: 10.1007/s00299-017-2137-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeted gene disruption coupled with metabolic screen approach to uncover the LEAFY COTYLEDON1-LIKE4 (L1L4) function in tomato fruit metabolism

Abstract: Functional analysis of tomato L1L4 master transcription factor resulted in important metabolic changes affecting tomato fruit quality. Tomato fruits from mutant lines bearing targeted disruption of the heterotrimeric nuclear transcription factor Y (NF-Y) transcription factor (TF) gene LEAFY-COTYLEDON1-LIKE4 (L1L4, NF-YB6), a master regulator of biosynthesis for seed storage proteins and fatty acids, were evaluated for metabolites content and morphology. Metabolic screens using LC-MS/MS-based analysis and physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 104 publications
0
11
0
Order By: Relevance
“…Half of the peel and pulp (including seeds) of each of the 10 fruits from each replicate was pulped with an UltraTurrax T 18 (IKA, Germany) for 2 min, then centrifuge for 5 min at 5,000 rpm (Gago et al, ). The resulting juice was used for the assessment of pH, titratable acidity (TA) and total soluble solids content (TSS).…”
Section: Methodsmentioning
confidence: 99%
“…Half of the peel and pulp (including seeds) of each of the 10 fruits from each replicate was pulped with an UltraTurrax T 18 (IKA, Germany) for 2 min, then centrifuge for 5 min at 5,000 rpm (Gago et al, ). The resulting juice was used for the assessment of pH, titratable acidity (TA) and total soluble solids content (TSS).…”
Section: Methodsmentioning
confidence: 99%
“…So far, a large number of functional and regulatory genes implicated in abiotic and biotic stress responses have been identified in a diversity of plants. In particular, we characterized some functional or regulatory genes controlling metabolism of N, PAs, ethylene, and abscisic acid that are involved in various biological processes [22,33,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72].…”
Section: Major Genes Involved In Abiotic and Biotic Stress Responsesmentioning
confidence: 99%
“…Indeed, silencing particular NF‐YB genes led to pink‐coloured fruits with colourless peels (Figs 2a, 3a). Previous studies have reported that L1L4 (NF‐YB6) affects tomato fruit quality (Gago et al ., 2017), high‐level expression of a tomato HAP5a gene can reduce the flowering time of Arabidopsis (Ben‐Naim et al ., 2006) and SlNF‐YA‐L1 is implicated in the regulation of salt and osmotic stress tolerance (Filichkin et al ., 2018). Combined with our observation on colour change in transgenic fruits (Figs 2a, 3a, S3a), these results indicated that NF‐Y complexes composed of different subunits may regulate different biological processes.…”
Section: Discussionmentioning
confidence: 99%